Development of Flexible Bone Grafts - Gameiro, Rafael Capêlo Leite (2018)
With the aging of world’s population, diseases and bone related problems are becoming more frequent. Bone grafts are normally used in the treatment and repair of bone defects. The aim of this project was to develop a flexible bone graft in order to be adjustable to the patient's problem. The development of this product consisted in combining a natural protein, type I collagen, extracted from bovine tendon, with β-TCP, a calcium phosphate. The composition of this product was 10:90 wt%, respectively. Its production focused in a lyophilization cycle and posteriorly Dehydrothermal crosslinking, using three different treatments: 24, 48 and 72h. The products were characterized by XRD, FTIR, SEM, Archimedes Method, compression tests and TGA-DSC. All the composites manufactured showed a porous structure, revealing values in the range of 84 to 87%.The β-TCP particles were homogeneously distributed and overlapped in the collagen matrix. The crystalline phases of the samples were studied and the presence of β-TCP was identified. Molecular groups were identified as referring to collagen and β-TCP. The observed amide peaks I, II, III, A and B tend to be less pronounced when the crosslinking exposure time increases, while the phosphate groups were observed with clarity. The products exhibited Young's Modulus values ranging from 180 to 200 kPa. These values tend to increase when the exposure time of crosslinking increases. Mass losses were not considered significant for the crosslinked products, varying between 8 and 11%. However it was shown that the Dehydrothermal crosslinking minimizes mass losses when compared to composites without this treatment. It is possible to conclude that a flexible bone graft was successfully developed. For that reason, the collagen / β-TCP composite showed a better handling when compared to calcium phosphates bone grafts.